The Effectiveness of Choice Theory in Quality of Life and Resilience of Drug Users - somaye najafi; farh nadri; ali sahebi (Drug Control Headquarters, Research and Education Office, 2015)
Objective: This study was an attempt to evaluate the effectiveness of the application of choice theory in quality of life and resilience of male drug users of Tehran. Method: An experimental research design with pretest-posttest and control group was employed for this study wherein 40 drug users were randomly selected from a governmental center. The experimental group was exposed to twelve 90-minute intervention sessions of choice theory. Then, both groups were tested. The follow-up was performed two months later. Quality of life questionnaire and Connor-Davidson resilience scale were used for data collection purposes. Results: The results of this study showed that the application of choice theory had an impact on quality of life and resilience. This finding was actively present in the follow-up, as well. Conclusion: This Method can be used to treat addicts.